The effect of long-term clopidogrel use on neointimal formation after percutaneous coronary intervention - Akbulut, M; Ozbay, Y; Karaca, I; Ilkay, E; Gundogdu, Z; Arslan, N (Lippincott Williams & Wilkins, 2004)
Objective The purpose of this study was to evaluate the long term effect of clopidogrel-based antiplatelet therapy on neointimal formation. Methods This study comprised 78 patients with typical stable angina pectoris or documented myocardial ischaemia, and with only one angiographic lesion in one native coronary artery undergoing successful stent implantation without predilatation with C-reactive protein levels less than or equal to 5 mg/l at 72 h after the procedure. All patients received dual antiplatelet therapy with 75 mg/day clopidogrel and 300 mg/day aspirin for four weeks. Clopidogrel was switched to isochronous placebo in half of the patients (n = 39) at the end of the fourth week. This allocation was maintained for 20 weeks, and at week 24 of the study, coronary angiography and intravascular ultrasound imaging were performed again in all cases in order to evaluate the changes that had occurred in the in-stent neointimal formation; rates of restenosis were also recorded Results At the end of the follow-up period, angiographic stenosis diameter and restenosis rates were smaller in the clopidogrel group than in the placebo group (23.3% versus 35.6%, p = 0.05 and 5.12% versus 10.25%; p = 0.03 respectively); the intravascular ultrasonographic neointimal cross sectional area was also smaller in the clopidogrel group (3.6 +/- 2.7 mm(2) versus 5.2 +/- 2.5 mm(2), p = 0.03). Conclusions Long-term clopidogrel administration significantly reduced neointimal formation at the stent site as well as reducing major clinical events in patients who did not develop high-risk systemic inflammatory response after percutaneous coronary intervention. (C) 2004 Lippincott Williams Wilkins.
Keywords: percutaneous coronary intervention; clopidogrel; neointimal formation